Research of Dynamic Load Spectrum Simulation Method of Hybrid Electric Vehicle Transmission System based on RPC - Kaihua Cheng (Jixie chuandong)
In order to evaluate the fatigue durability of the hybrid vehicle driveline， the load simulation test system is used to simulate the dynamic load spectrum of the vehicle on the actual road. The dynamics analysis of the load simulation system is carried out to establish an integrated analysis model of the load simulation system. The dynamic load spectrum is collected in the test field， and analyzed and processed to determine the load spectrum bandwidth of the load simulation system. In order to improve the simulation accuracy of the dynamic load spectrum of the load simulation system， a dynamic load spectrum simulation method based on RPC （Remote Parameter Control） is proposed， which reduces the tracking error by simulation iterative control. After 15 simulation iterations， the speed and torque control accuracy （1.03%， 2.38%） are improved by 5.72% and 6.94% respectively compared with the conventional PID control （6.75%， 9.32%）. The dynamic load spectrum response after iteration， the error can be controlled within 5%， which can meet the indoor bench durability test requirements.